2017
DOI: 10.7150/jca.16856
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Folate Receptor-positive Circulating Tumor Cells Detected by Ligand-targeted Polymerase Chain Reaction in Lung Cancer

Abstract: Background: As the heterogeneity of CTCs is becoming increasingly better understood, it is clear that identifying particular subtypes of CTCs would be more relevant.Methods: We detected folate receptor (FR)-positive circulating tumor cells (FR+-CTCs) by a novel ligand-targeted polymerase chain reaction (LT-PCR) detection technique.Results: In the none-dynamic study, FR+-CTC levels of patients with lung cancer were significantly higher than controls (patients with benign lung diseases and healthy controls). Wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 30 publications
5
50
1
1
Order By: Relevance
“…ABI7300 instruments (Life Technologies, Carlsbad, CA, USA) were used to collect PCR signals and data. The reaction conditions were: 95°C, 2 minutes; 40°C, 30 seconds; 72°C, 30 seconds; 8°C, 5 minutes; 40 cycles, 95°C, 10 seconds; 35°C, 30 seconds; and 72°C, 10 seconds …”
Section: Methodsmentioning
confidence: 99%
“…ABI7300 instruments (Life Technologies, Carlsbad, CA, USA) were used to collect PCR signals and data. The reaction conditions were: 95°C, 2 minutes; 40°C, 30 seconds; 72°C, 30 seconds; 8°C, 5 minutes; 40 cycles, 95°C, 10 seconds; 35°C, 30 seconds; and 72°C, 10 seconds …”
Section: Methodsmentioning
confidence: 99%
“…These studies have shown that by using folate receptor as a marker it is possible to discriminate between NSCLC patients, individuals with benign lung disease and healthy subjects. A sensitivity up to 77.7% and a specificity up to 89.5% for the diagnosis of NSCLC was reported (7,9). However, it must be emphasized that the sensitivity was higher for stage IV patients, while it was <70% in stage I.…”
Section: Ctc As a Diagnostic Marker In Nsclcmentioning
confidence: 99%
“…Different studies have used the folate receptor transcript as a marker to identify the CTC (7)(8)(9). In fact, folate receptor is often expressed in NSCLC cells whereas its levels of expression are usually low in blood cells.…”
Section: Ctc As a Diagnostic Marker In Nsclcmentioning
confidence: 99%
“…Although CTCs were observed more than 100 years ago, for the first time, their clinical significance has recently recognized. 15 Detection of CTCs might be difficult because of their rare numbers comparing with the number of leukocytes (~1 CTC per 10 5 -10 8 leukocytes) in blood. 13 Although there are many different techniques applied for the detection of CTC, only the CellSearch system which has been approved by the U.S. Food and Drug…”
Section: Discussionmentioning
confidence: 99%